2017
DOI: 10.1155/2017/6101609
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Valproic Acid Affect Early Neurogenesis of Human Amniotic Fluid Stem Cells from Myelomeningocele

Abstract: Myelomeningocele (MMC) is a severe type of neural tube defect (NTD), in which the backbone and spinal canal do not close completely during early embryonic development. This condition results in serious morbidity and increased mortality after birth. Folic acid significantly reduces, and conversely, folate antagonist methotrexate (MTX) and valproic acid (VPA) increase the occurrence of NTDs, including MMC. How these pharmacological agents exactly influence the early neurulation process is still largely unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Previous studies also showed that histone methylation modi cation could directly or indirectly activate and inhibit gene expression, thereby affecting embryonic development [30]. It was revealed that valproic acid caused the increased of H3K4me3, and decreased of H3K9me3 in the NTDs mouse model, respectively [31]. In our study, the results showed that histone methylation modi cation was signi cantly decreased in ethionine-induced NTDs embryos, which were consistent with the alteration of H3K79me3 and H3K27me3 in human NTDs samples [27,32].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies also showed that histone methylation modi cation could directly or indirectly activate and inhibit gene expression, thereby affecting embryonic development [30]. It was revealed that valproic acid caused the increased of H3K4me3, and decreased of H3K9me3 in the NTDs mouse model, respectively [31]. In our study, the results showed that histone methylation modi cation was signi cantly decreased in ethionine-induced NTDs embryos, which were consistent with the alteration of H3K79me3 and H3K27me3 in human NTDs samples [27,32].…”
Section: Discussionsupporting
confidence: 87%
“…There are several hypotheses on how VPA causes NTDs, including alterations in folate metabolism, increase in reactive oxygen species, and epigenetic dysregulation ( 30 - 34 ). For instance, the effect of VPA as a folic acid antagonist is primarily supported by a comparative analysis between the effects of methotrexate and VPA ( 35 - 37 ). This is also supported by the observation that folic acid rescued VPA-induced defects in zebrafish embryos as well as in in vitro neural tube models ( 27 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of neural differentiation has been shown in previous in vitro studies. 25,49 Some parallels can be drawn with human studies of MTX exposure, as fetal MTX syndrome revealed a higher number of microcephaly cases than expected, and regulation of neural crest cell differentiation could result in potential neural crest-related malformations (such as the typical facial dysmorphic features). However, this remains speculative.…”
Section: Discussionmentioning
confidence: 99%